How to Evaluate Disability - Sohail, Zohaib; Bailey, Rahn K.; Richie, William D. (Frontiers in Psychiatry, 2013)
A disability assessment for non-therapeutic reasons is the most common evaluation requested of treating psychiatrists. Mental disorders affect approximately 20 percent of Americans each year. People who are unable to work need some financial assistance. As part of the system, it’s our goal to assist them in this process. When a disability claim is filed, psychiatrists take into account the individual’s impairments and disabilities. A psychiatrist’s evaluation of disability involves knowledge and experience. There are many ethics related challenges, especially when performing disability evaluation of their own patients. Disability training should therefore be part of residency curriculum for training of psychiatry residents.